Prevalence and incidence of oral cancer in low‐ and middle‐income countries: A scoping review - Shrestha, Aamod D.; Vedsted, Peter; Kallestrup, Per; Neupane, Dinesh (European journal of cancer care, 2020)
Introduction Oral cancer is common cancer in many low‐ and middle‐income countries (LMICs) with a low five‐year survival rate. It is among the four most common types of cancer in South East Asia region. In South‐Central Asia, lip and oral cavity cancer is the second most common cancer according to the specific cancer types. Methods This scoping review intended to investigate published studies on the current prevalence and incidence of oral cancer in LMICs. The review was conducted applying the search words “Oral Cancer” and “Mouth neoplasm” as the Medical Subject Heading (MeSH) major topic and “Epidemiology” and (“prevalence” OR “incidence”) as the MeSH subheading; the search was supplemented by cross‐references. Included studies met the following criteria: original studies, reporting of prevalence or incidence rates, population‐based studies, studies in English language and studies involving humans. Results The sample sizes ranged from 486 to 101,761 with 213,572 persons included. Buccal mucosa is one of the most common sites of oral cancer, associated with the widespread exposure to chewing tobacco. The incidence is likely to rise in the region where gutkha, pan masala, pan–tobacco and various other forms of chewing tobacco are popular. Conclusion This review contributes to useful information on prevalence and incidence estimates of oral cancer in LMICs.